THE EFFECT OF TRANSFER PRICING, LEVERAGE AND COMPANY SIZE ON CORPORATE TAX AVOIDANCE IN AGRICULTURAL COMPANIES LISTED IN INDONESIA STOCK EXCHANGE - Sitompul, Thomson; Ong, Jerrico (Jurnal Penelitian Akuntansi (JPA), 2024)
In Indonesia itself, the practice of tax avoidance has been widely practiced and Indonesia is one of the developing countries with the greatest losses caused by tax avoidance. Therefore, transfer pricing is used by companies to minimize the amount of tax paid through engineering prices transferred between divisions. In terms of leverage, Interest expenses are included in expenses that can be deducted from taxable income. This action is used by company managers to reduce the tax obligations borne by the company and is included in tax avoidance. A company with relatively large total assets indicates that the company has a large size so that it has great potential to gain maximum profits as well as its tax burden. The population used in this research is all 24 agricultural sector companies listed on the Indonesian Stock Exchange. The sampling technique used purposive sampling which is 63 samples in total. The results of the study indicate that Transfer Pricing has no significant impact in agricultural companies listed on the Indonesia Stock Exchange (IDX). Leverage has significant impact in agricultural companies listed on the Indonesia Stock Exchange (IDX). Company Size has a negative significant impact in agricultural companies listed on the Indonesia Stock Exchange (IDX). Transfer Pricing, Leverage, Company Size do not have simultaneous effect and significant impact on tax avoidance.